Tasawuf Dalam Peradaban Islam: Apresiasi dan Kritik - Kautsar Azhari Noer (Universitas Islam Negeri Mataram, 2006)
It is undeniable that Islamic mysticism (tasawuf) has important contribution to Islamic civilization development. But, its complicated and ‘wilderness’ teaching makes it always becomes the object of criticism especially from the scholars of fiqh. Using historic-conceptual trace, this writing reveals the role of Islamic mysticism in developing Islamic civilization such as in philosophy, education, psychology, literature, dance and music. The fundamental concept of sufi wahdah al-Wujûd (the oneness of Being) gives contribution to solve problems related to modern science especially physic. Islamic mysticism like modern physic, teaches the awareness of unity and interrelationship among all things and events, occurrence of all phenomena in this universe as a manifestation of a basic unity. However, its intricate teachings which is difficult to accept by ordinary people frequently lead to misunderstanding. To make thing worst, some practitioners of Islamic mysticism commercialize the spiritual value of the Islamic mysticism for a little price.